The Meaning of Happiness in the Philosophy of Stoicism and Its Relevance to Islamic Guidance - Faiz Al Faroqi; Safrodin Safrodin; Ema Hidayanti; Komarudin Komarudin; Widayat Mintarsih (KURAS Institute, 2025)
Happiness is a fundamental goal in human life, yet its meaning is often interpreted in various ways. This study aims to examine the concept of happiness in Stoic philosophy and its relevance to Islamic Guidance. This research employs a qualitative approach through library research, analyzing the thoughts of Stoic philosophers such as Epictetus, Seneca, and Marcus Aurelius, and connecting them with principles of Islamic Guidance derived from the Qur'an and Hadith. The findings reveal that happiness in Stoicism is understood as a state of inner peace attained through rational deliberation, disciplined self-mastery, and equanimous acceptance of the uncontrollable. In contrast, Islamic Guidance views happiness as a harmony between spiritual and social dimensions, realized through faith, worship, and submission to the will of Allah (tawakkul and ridhā). There is a significant convergence between the two, particularly in the aspects of self-mastery, acceptance of destiny, and the search for deeper meaning in life. The study shows that Stoic values can enrich Islamic counseling methods, especially in assisting individuals to achieve inner calm amid the pressures of modern life. The integration of Stoic principles with Islamic spiritual approaches may serve as an effective guidance strategy in shaping individuals who are resilient, patient, and wise.